The Consciousness Elements of Eco-Theological Education in Pesantren's Culture - Ahmad Aziz Fanani; Andi Susilo; Imam Wahyono (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The increasingly urgent global ecological crisis demands a holistic approach, including spiritual and moral dimensions in education. This study focuses on how elements of eco-theological consciousness are cultivated within the educational culture of Islamic boarding schools (pesantren), and how these elements shape the ecological behavior of pesantren communities. In this context, pesantren, as traditional Islamic educational institutions, hold significant potential to instill ecological consciousness grounded in religious values. This interdisciplinary research integrates theological, sociological, and educational approaches, which are still rarely examined in a comprehensive manner within the pesantren context. Employing a paradigmatic approach grounded in constructivism and interpretivism, this qualitative study was conducted at two pesantren recognized for their strong ecological culture: Subulussalam in Banyuwangi and Nurul Qornain in Jember. The findings suggest that eco-spiritual consciousness in pesantren is built upon two main pillars: cognitive and value-based elements. At Nurul Qornain, ecological cognition stems from fiqh-based (Islamic jurisprudential) understanding, while at Subulussalam, it arises from theological aesthetics. Both pesantren also demonstrate the internalization of values that shape a collective ethos—cleanliness as worship and beauty as an expression of faith. Therefore, ecological consciousness in pesantren is not merely a matter of verbal instruction, but a cultural praxis that is sustainably transmitted across generations. These findings make a significant contribution to the development of faith-based environmental education.